Legal Status of Inheritance of Children From Adultery in Indonesia - Delfina, Dinda (CV. Ulil Albab Corp, 2025)
This study analyzes relevant legislation, court decisions, and literature, complemented by a case study of Ridwan Kamil to illustrate practical implementation challenges and social implications. Using a normative legal approach, this study highlights barriers such as social stigma, family rejection, and regulatory gaps, while emphasizing the need to harmonize religious norms with state law. with a focus on the limitations set by Article 43 paragraph (1) of Law Number 1 of 1974 concerning Marriage Constitutional Court Decision Number 46/PUU-VIII/2010. The findings offer a comprehensive legal analysis and policy recommendations aimed at promoting inclusive family law reform that upholds constitutional principles of justice and non-discrimination. This study contributes to the development of fairer legal protection for children born out of wedlock in Indonesia, by promoting their rights to maintenance and inheritance regardless of marital registration status.